Associations of mindfulness with depressive symptoms and well-being in older adults: the moderating role of neuroticism. (3rd April 2019) - Elliot, Ari J.; Gallegos, Autumn M.; Moynihan, Jan A.; Chapman, Benjamin P.
ABSTRACT: Objective: To investigate whether observed interactions of mindfulness with the personality trait neuroticism extend to older adults and to aspects of psychological functioning other than depressive symptoms, and whether effects of mindfulness training in this population depend on levels of neuroticism. Method: We performed a secondary analysis of data from a randomized controlled trial of Mindfulness-Based Stress Reduction (MBSR) for community-dwelling older adults. We investigated whether neuroticism moderates associations of dispositional mindfulness with various aspects of psychological and physical functioning at baseline, as well as effects of MBSR on these outcomes. Results: Significant two-way interactions showed that greater mindfulness was associated with fewer depressive symptoms and less negative affect at baseline in individuals with average or higher levels of neuroticism. In contrast, mindfulness was associated with greater positive affect and vitality and fewer physical symptoms regardless of the level of neuroticism. There were no effects of MBSR on these outcomes at any level of neuroticism. Conclusion: Mindfulness may be more protective against psychological ill-being in older adults with higher levels of neuroticism, but conducive to positive psychological and physical well-being regardless of this personality trait. The potential moderating role of neuroticism should be further evaluated in studies of mindfulness-based interventions in older adults.